(untitled) (European Journal of Pure and Applied Mathematics, 2023)
In this paper, we introduce the subclass of star-like functions with respect to symmetric conjugate points associated with the sine function. Some coefficient functionals for this class are considered. Bounds of Taylor coefficients, logarithmic coefficients, and the Hankel and Toeplitz determinants whose entries are logarithmic coefficients are provided.